Understanding life - Adler, Alfred, 1870-1937.; Brett, Colin (Center City, Minn. : Hazelden, 1998)
Describes the main concepts of Individual Psychology, a theory of human behavior developed by psychology pioneer Alfred Adler, and applies the principles of the theory to topics such as inferiority complex, lifestyle, childhood memories, dreams, social adjustment, and intimate relationships.
Originally published: The science of living. New York : Greenberg, c1929.
Includes bibliographical references (p. 143-144) and index.
Adult
Keywords: Psychoanalysis; Psychology; Psychoanalysis; Psychology